One health approach to address zoonotic diseases - Divya Aggarwal; Anandhi Ramachandran (Wolters Kluwer Medknow Publications, 2020)
The world of animals, humans, and environment is interlinked, giving rise to a number of benefits as well as a spread in zoonosis and multifactorial chronic diseases. With the emergence of antimicrobial resistances and environmental pollution, addressing these diseases needs an interdisciplinary and intersectoral expertise. "One Health (OH)" refers to such collaboration between local, national, and global experts from public health, health care, forestry, veterinary, environmental, and other related disciplines to bring about optimal health for humans, animals, and environment. The concept of OH is still in embryonic stage in India and increasingly gaining importance. The Government of India has taken some initiatives to tackle burgeoning problems such as antimicrobial resistance, zoonotic diseases, and food safety using the OH approach, but there are several challenges at the level of implementation. The major bottlenecks in implementing OH include absence of a legal framework to implement OH, poor coordination among different governmental and private agencies, lack of proper surveillance of animal diseases, poor data-sharing mechanism across sectors, and limited budget. Implementing systematic zoonotic surveillance; regulated antibiotic use among humans and animals; development of a zoonotic registry in the country; constitution of a wide network of academic, research, pharmaceutical, and various implementation stakeholders from different sectors is the need of the hour to effectively use OH in order to combat increasing zoonotic diseases.